Happy Software: An interactive program based on an emotion management model for assertive conflict resolution - Filella, Gemma; Ros-Morente, Agnès (Frontiers in Psychology, 2023)
Emotions are key to conflict resolution: to resolve conflict situations assertively, we must be able to manage the emotions that cause them. After a detailed analysis of the relevant theoretical framework, this paper presents a theoretical emotion management model aimed at assertive conflict resolution. The model, which is described step by step, has been gamified, implemented, and assessed in a population aged 8 to 16. The model is divided into 4 steps or phases. The first is emotional awareness, which consists of understanding and legitimating emotions; the second focuses on reducing emotional intensity and impulsivity; the third encompasses the use of different emotion regulation strategies, and the fourth and final step is assertive communication. Training in this process results in better emotion management, which both eventually leads to greater wellbeing and a more positive assessment of new conflicts and aids in the assertive resolution thereof. The final section of the paper summarizes the most important evidence and outcomes of the use of the Happy software so far.